Soil Salinity Controls Relative Abundance of Specific Bacterial Groups Involved in the Decomposition of Maize Plant Residues - De León-Lorenzana, Arit S.; Delgado-Balbuena, Laura; Domínguez-Mendoza, Cristina A.; Navarro-Noya, Yendi E.; Luna-Guido, Marco; Dendooven, Luc (Frontiers in Ecology and Evolution, 2018)
Extreme salinity and alkalinity in soil is known to inhibit organic material decomposition and affect the bacterial community structure involved in its mineralization. Regular flooding of these soils will reduce salinity, which will alter the bacterial community involved in organic material mineralization. Soil of the former lake Texcoco with electrolytic conductivity (EC) 157.4 dS m-1 and pH 10.3 was flooded monthly, amended with maize plant residue or its neutral detergent fibre (NDF; mostly (hemi)cellulose and some lignin), while C mineralization and the bacterial community structure was monitored by means of 454 pyrosequencing of the 16S rRNA gene. The EC of the soil dropped from 157.8 to 1.7 dS m-1, but the pH (10.3) did not change significantly over time. On the one hand, the relative abundance of some bacterial groups, e.g. Bacillus and Gammaproteobacteria, always increased when maize plants or NDF were applied to soil independent of the changes in soil characteristics, i.e. they always participated in the degradation of the organic material applied, while the relative abundance of other groups, e.g. Acidobacteria, Alphaproteobacteria, Chloroflexi, Clostridia, Deltaproteobacteria, Gemmatimonadetes, Planctomycetes and Verrucomicrobia, always decreased compared to the unamended soil. On the other hand, the increase or decrease of the relative abundance of other bacterial groups when organic material was applied to soil was influenced by the changes in soil characteristics. For instance, the relative abundance of the Actinomycetales, Halomonas and Prauseria, did not increase when organic material was applied to soil with a high salt content, but did when the salt content was lowered while that of the Betaproteobacteria and Pirellulales increased when the salt content was high, but not when it was lowered. Application of the NDF generally had a similar effect on the bacterial community structure as when maize plants were applied. It was found that the capacity of some bacterial groups to degrade organic material was not affected by soil salt content, while that of others was stimulated or suppressed.